Native American Lifestyles: Issues for Human Services Professionals - LLoyd Brightman; Gail Dana; Stephen Marks (Journal of Research in Rural Education, 1983)
Educators and human service workers who experience difficulties in communicating with Native American students, parents and clients may be overlooking important subcultural differences which this group displays. A survey of 180 American Indian families living on and off reservations in Maine and in Metropolitan Boston showed differences in life style, when compared / with a control group of low income white families, in the areas of property ownership, competition, consistency of household membership , and in friendship and neighboring patterns, all of which have implications for educalOrs and human service workers.